Proceedings of the Sixth ACM Conference on Recommender Systems 2012
DOI: 10.1145/2365952.2365973
|View full text |Cite
|
Sign up to set email alerts
|

Local implicit feedback mining for music recommendation

Abstract: Digital music has experienced a quite fascinating transformation during the past decades. Thousands of people share or distribute their music collections on the Internet, resulting in an explosive increase of information and more user dependence on automatic recommender systems. Though there are many techniques such as collaborative filtering, most approaches focus mainly on users' global behaviors, neglecting local actions and the specific properties of music. In this paper, we propose a simple and effective … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
26
0
2

Year Published

2013
2013
2023
2023

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 35 publications
(28 citation statements)
references
References 28 publications
0
26
0
2
Order By: Relevance
“…ey move the underlying model from a matrix completion task toward a Markov Decision Process (MDP). Businesses encounter session-based recommender systems in domains including music [38], products [18], and news [23]. Deep learning architectures have been applied to session-based recommendation (cf.…”
Section: Session-based Recommendationmentioning
confidence: 99%
“…ey move the underlying model from a matrix completion task toward a Markov Decision Process (MDP). Businesses encounter session-based recommender systems in domains including music [38], products [18], and news [23]. Deep learning architectures have been applied to session-based recommendation (cf.…”
Section: Session-based Recommendationmentioning
confidence: 99%
“…Compared with traditional SVD++ and Original AutoSVD++, our e cient training algorithm achieves a signi cant reduction in time complexity. Generally, the optimized AutoSVD++ performs R times be er than original AutoSVD++, whereR denotes the average number of items rated by users [13]. Meanwhile, compared with biased SVD model, the incorporated items Cae(C i ) and o set ϵ i does not drag down the training e ciency.…”
Section: Overall Comparisonmentioning
confidence: 99%
“…al. [15] suggested to use implicit feedback collected from a user during a short time period to extract her local preference, which is to represent her taste during the next few minutes. It has been shown that implicit feedback from users can be used for news recommendation [7], and Parra et al [16] showed a strong relation between users' implicit feedback and explicit ratings.…”
Section: Related Workmentioning
confidence: 99%